Constructing provable secure broadcast encryption scheme with dealership. (May 2021) - Acharya, Kamalesh; Dutta, Ratna
Abstract: Broadcast encryption with dealership (BED) introduced by Gritti et al. (2015) is a proficient cryptographic primitive which involves a third party called as a dealer and creates a business opportunity for the dealer in broadcast services. Designing a BED is a tough task due to its various security requirements. Existing BED of Gritti et al. (2015). requires to get the user's response to detect a dishonest dealer which is not practical in many cases. Acharya and Dutta solved the problem and proposed a BED scheme using random oracles. This brings up the question of whether it is possible to generate a secure BED without using the random oracle. Fortunately, we have found positive results. We have proposed two constructions in the standard model. Our first scheme is semi-static secure whereas the second one is the first adaptive secure construction in the standard model. All of our constructions provide group privacy by hiding the group of users and provide the maximum number of accountability by restricting the dealer from generating a group token involving a set of users having cardinality greater than a threshold value. We have provided concrete security proof of both of our constructions under key indistinguishability security game. Moreover, we have implemented our schemes and compared with existing schemes.